ICT labor, software usage, and productivity: firm-level evidence from Turkey - Tastan, Hueseyin; Gonel, Feride (SPRINGER, 2020)
This paper examines the impact of information and communication technology (ICT) on firm-level productivity in Turkey using a novel longitudinal data set. We combine two firm-level data sets compiled by the Turkish Statistical Institute and construct an unbalanced panel data set covering the period 2007-2014. Our data set matches firms in the ICT Usage in Enterprises Survey to the Annual Industry and Service Statistics Survey that includes data on production factors and firm characteristics. We estimate production functions augmented by ICT labor, software investments, and indicators for the usage of enterprise system applications including ERP, CRM, and SCM. Our results confirm that there is a positive relationship between firm-level productivity and ICT use. Empirical findings support the complementarity hypothesis between ICT labor and software usage variables. This result implies that the productivity contribution of ICT labor is larger in firms using specialized software. Accordingly, firms need to invest in ICT labor to reap the benefits from enterprise software investments. We also estimate our models using sub-samples based on size and sector. While the elasticity of ICT labor is higher in small and medium-size firms, larger firms have greater marginal product than smaller firms. Our results also suggest that the strength of the link between ICT and productivity may be different across sectors. In particular, we find that the productivity contribution of ICT labor is higher in the services than the manufacturing sector.
Keywords: ICT; Productivity; Software; ERP; SCM; CRM; WORKPLACE ORGANIZATION; INFORMATION-TECHNOLOGY; SKILLED LABOR; IMPACT; INNOVATION; ADVANTAGE; ADOPTION; PARADOX; WORKERS; DEMAND; Business & Economics; Mathematical Methods In Social Sciences